Genipin inhibits the growth of human bladder cancer cells via inactivation of PI3K/Akt signaling - Li, Zheng (Oncol Lett, 2018)
Genipin, a natural compound derived from the fruit of Gardenia jasminoides, possesses numerous biological properties. The aim of the present study was to investigate the anticancer effects of genipin in human bladder cancer. T24 and 5637 bladder cancer cells were treated with different concentrations of genipin (0–200 µM) and tested for cell viability, colony formation, cell cycle progression and apoptosis. A xenograft model of bladder cancer was established to determine the anticancer effect of genipin in vivo. The involvement of the phosphoinositide-3 kinase (PI3K)/Akt pathway in the action of genipin was examined. Genipin treatment significantly inhibited the viability and clonogenic growth of bladder cancer cells and inhibited the growth of T24 xenograft tumors, compared with vehicle controls (P<0.05). Genipin-treated cells exhibited a cell cycle arrest at the G0/G1-phase, which was accompanied by a deregulation of numerous cell cycle regulators. Genipin-treated cells demonstrated a significant increase in the percentage of apoptotic cells, loss of mitochondrial membrane potential, Bax translocation to the mitochondria and the release of cytochrome c to the cytosol. Additionally, genipin treatment significantly (P<0.05) reduced the phosphorylation levels of PI3K and Akt in bladder cancer cells. Importantly, genipin-mediated anticancer effects were reversed by the overexpression of constitutively active Akt. In conclusion, to the best of our knowledge, the present study demonstrates for the first time the growth inhibitory effects of genipin in bladder cancer cells, and indicates its potential as a natural anticancer agent for bladder cancer.